Fabrication of Digital Harmonic Vibration Practicum Using Phototransistor Sensor with Arduino-Uno Microcontroller - Marjoni Imamora Ali Umar; Dany Kurniawan; Novia Lizelwati (Postgraduate, University of Mataram, 2021)
The problem in the harmonic vibration practicum is in calculating time accurately. Commonly, the time counter used was a stopwatch, but it was unable to provide valid data. As a result, the student has difficulty seeing the relationship between concepts with practical results in the laboratory. To overcome these problems, in this study, we developed a harmonic vibration practicum tool that is equipped with a digital timer using an Arduino Uno microcontroller as a light sensor. An Arduino can be programmed via a PC according to the wishes of the developer. This study was development research using a 4-D model (Define-design-develop-dissemination). The define and design stages respectively to find problems in the harmonic vibration practicum tool. The tool is finally designed and then calibrated, validated, and practical. The calibration results show that the percentage difference for repetition measurement and comparison that values with theory was 0.008% and 3.98%, respectively. In addition, the validation results show an average percentage of 87% or very valid. For practicality, the result through a limited test of Physics students of IAIN Batusangkar in the second semester shows a very practical response with a percentage of 85.96%. Due to time constraints, the dissemination stages have not been carried out in this study.